2019
DOI: 10.31788/rjc.2019.1215023
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antibacterial Activity of Novel Vanillic Acid Hybrid Derivatives

Abstract: Vanillic acid (4-hydroxy-3-methoxy benzoic acid) is a dihydroxybenzoic acid derivative used as a flavoring agent. It is used in the synthesis of various active pharmaceutical ingredients such as Etamivan, Modecainide, Brovanexine, Vanitiolide, Vanyldisulfamide etc. In this paper, novel ester / hybrid derivatives of vanillic acid were synthesized and tested for potential antibacterial activity. This combinatorial synthesis of novel vanillic ester / hybrid derivatives can be a useful approach to generate potent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The methanol extract of E. elatior fruit contains bioactive compounds such as flavonoids, tannins, saponins, steroids, and triterpenoids [10]. The results of the study by Satpute et al reported that VA has antimicrobial, anti-inflammatory, and antioxidant properties [11]. In vitro studies showed that VA of 100 g/ml can inhibit the growth of S. enterica and S. mutans bacteria [12].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The methanol extract of E. elatior fruit contains bioactive compounds such as flavonoids, tannins, saponins, steroids, and triterpenoids [10]. The results of the study by Satpute et al reported that VA has antimicrobial, anti-inflammatory, and antioxidant properties [11]. In vitro studies showed that VA of 100 g/ml can inhibit the growth of S. enterica and S. mutans bacteria [12].…”
Section: Methodsmentioning
confidence: 99%
“…The results of the study by Satpute et al reported that VA has antimicrobial, anti-inflammatory, and antioxidant properties [11]. In vitro studies showed that VA 100 g/ml can inhibit the growth of S. enterica and S. mutans bacteria [12].…”
Section: Introductionmentioning
confidence: 99%
“…Many vanillic acid derivatives were produced and evaluated for different biological activities; vanillic Acid-oxadiazole Schiff bases showed interesting antibacterial activity (20) , novel ester-hybrid derivatives of vanillic acid examined for their antibacterial activity, the methyl vanillate derivative has significant anti-bacterial activity against tested Gram-positive and Gram-negative bacteria (21) . Other series of amide derivatives of vanillic acid exhibit promising selective inhibitory effects against α-amylase, and α-glucosidase enzymes (19) .…”
Section: Introductionmentioning
confidence: 99%
“…Research in the internal medicine department of RSUD Dr. Moewardi Surakarta in 1997 found that 130 (97%) out of 135 sepsis patients died [8]. In 2004, the mortality rate due to sepsis in RSUD Dr. Moewardi Surakarta reached 74 (83.1%) out of 89 sepsis patients [9]. Research conducted on January 2006-December 2007 in the PICU/NICU section of RSUD Dr. Moewardi Surakarta reported the incidence of sepsis of 33.5% with a mortality rate of 50.2% [10].…”
Section: Introductionmentioning
confidence: 99%